Effects of sawtooth side edges with different radial clearance angles on the cutting force in wood sawing. Issue 12 (10th December 2018) - Li, W.; Zhang, Z.; Luo, B.
Abstract: This study focuses on the influence of the sawtooth side edges on the cutting force and analyzes the functions of the side edges in wood sawing by separating the total cutting force into the force from the main edge and the side edges. Birch (Betula spp.) is used as the material for conducting the experiment. The influence of the sawtooth side edges with different radial clearance angles on the cutting force was studied by comparing closed cutting with open cutting for different cutting thicknesses, cutting speeds, and directions using a single sawtooth. The cutting force from the side edges accounts for 4.6 % to 16.9 % of the total cutting force when the sawing kerf is 1.6 mm. As the radial clearance angle increases or the cutting thickness decreases, the cutting force from the side edges and the proportion of the force from the side edges decrease. The cutting force from the side edges increases with an increase in the cutting speed but the cutting speed does not have a clear influence on the cutting force from the side edges. For the same radial clearance angle, the cutting force from the side edges is the largest for the (0°–90°), followed by the (90°–0°) and the (90°–90°).